PREVENTION OF DENTAL CARIES IN THE CONDITIONS OF ECOLOGICAL POLLUTION - I.V. Kovach; H.V. Shtompel; Ye.N. Dychko; A.V. Verbytska (Ukrainian Medical Stomatological Academy, 2018)
Modern domestic preventive dentistry has success in the theory of the origin and development of major dental diseases, practice of treatment, including dental caries, and uses these results to prevent children's diseases in the country. However, the desired effectiveness of preventive measures have not been achieved primarily among the population and individual level, taking into account some specific characteristics of residence region, etiology and pathogenesis of the demineralization phenomena of hard dental tissues in different periods of child's development. Adverse environmental conditions and technogenic character are not taken into account, when air, soil and groundwater are oversaturated with environmental contaminants and toxicants. They cause fatal breakage in biochemical reactions and metabolic processes in childhood and at a young age, when defective dental health brings a lot of problems in the adult period of life, and, as a result, reduces the life. Investigation of dental health had been conducted in 251 preschool age children (first age group consisted of 3-4 years-old, II group consisted of 5-6 - years-old with 123 and 128 people respectively). In addition, all the observed children were divided into two groups depending on the use of prophylactic anti-caries interventions: the basic group was in compliance with the "Program- maximum" and control the "Program- minimum". Approximately 60 members were in the monitoring teams of different age groups. The "Program-minimum" included measures of general health, balanced diet with the significant restriction of carbohydrate and perform twice a day hygiene actions in the oral cavity. The "Program - maximum" also included the ingestion of calcium citrate and amino acids with SH-group of methionine. Such treatment and prophylactic complex has the adaptive, antioxidant, antidote and immune resolving action. It makes sense for neutralization of eco toxicants - heavy metals in the area of children's residence. It was found that level of Fe and Zn was in the threatening degree of content, and Cd is moderate in the living environment of the examined children. It provokes and enhances the glycolytic processes in the oral cavity. Harmful effect of toxicants in the oral cavity, and also in a children's organism as a whole, was clearly fixed in the mineralization of the skeleton flat bones of children. It was revealed with densitometry of the calcaneus that 53 individuals had  indicators, particularly BUA. They indicated the weakening of the skeleton mineralization. It indirectly pointed to problems in the hard tissues of the teeth. However, the use of treatment and prophylactic complex improved the bone structures density. The level of calcium and phosphate in the oral fluid of the observed individuals had recovered to optimal after three years of use of treatment and prophylactic complex, contributed to effective secondary mineralization both in temporary and in permanent teeth. Thus, the use of treatment and prophylactic complex in people of the basic group allowed quite convincingly and positively to impact on the incidence of caries of deciduous and permanent teeth. The rate of growth of dental caries intensity after three years of preventive interventions in the basic group was three times less than in the control group. At the same time, the caries preventive efficacy was 59-62%, and this is a very positive indicator. These results are evidence of proven necessity of prophylactic of dental health correction in children years of those people who reside in areas with a very complex technogenic environment due to metallurgical plants located in the Prydniprovsk region.